A Critical Prolegomena. Value-Form & The Necessity of a Historical Subject - Knowlton Jr., Kenneth (Bollettino Filosofico, 2025)
This work serves as a critical prolegomena for the development of a dialectical materialist relational ontology. Through an immanent critique of Moishe Postone’s interpretation of the Hegel-Marx relation and his disavowal of reading Marx ontologically, I demonstrate the necessary connection between Marx’s ontological presuppositions, epistemological framework, and his political-economic critique. My claims focus on the theoretical relationship between certain transhistorical assumptions and their relevance for a critical analysis of the historically specific social form of capital. In combining value-form analysis with Marx’s original epistemological reconfiguration of subject-object relations, as well as his relational ontology, I defend the necessity of retaining, methodologically, a historical subject – the “class of producers” – through which the project of revolutionary social transformation is envisioned. Keywords: Dialectical Materialism, Epistemology, Marxism, Materialist, Relational Ontology, Value-Form